Impact assessment of DG in distribution systems from minimization of total real power loss viewpoint by using optimal power flow algorithms - Bindeshwar Singh; Bindu Jee Gyanish (Energy Reports, 2018)
This paper presents the enhancement and impacts of the system losses, voltage profile and cost by using distributed generations (DGs) of different size in distribution network. Distributed Generation (DGs) is expected to play a key role in the residential, commercial and industrial sectors of the power system. Distributed Generation (DG) provides an alternative to the traditional electricity sources and can also be used to enhance the current electrical system. DG produces a series of important influence on the distribution network. It mainly introduces four effect areas, namely, distribution network real power loss, voltage, distribution grid planning and relay protection. In this analysis, load flow method is used for optimization of objective function for minimization of total real power loss and reactive power loss of the system. The work is focused on analyzing the impact of DG installation on distribution network operation including system voltage profile analysis, real and reactive power losses and cost of the system. First, various sizes of DG penetration levels and the impact of distributing the DG across the bus where load is maximum are explored. Secondly, the real power losses of the system are analyzed. Thirdly, the voltage profile and cost of the system are analyzed. The proposed methodology has been tested for IEEE-14 bus distribution test system. This work is also helpful for practitioner whose are working in the fields of renewable energy sources.
Keywords: 330; Cost; Distributed generation (DG); Distribution systems; Optimal size and location of DG; Power flow analysis; Reactive power loss; Real power loss; Voltage profile